Patients' duties: the missing element in European healthcare law - Sandland, Ralph; Lobato de Faria, Paula (Maklu, 2017)
This chapter asks why there is such a developed notion of patients' rights, but such an underdeveloped notion of patients' duties. It also considers the advantages and disadvantages of formally stating patients' duties in legal form.